(untitled) (Experimental biology, 2021)
Fish completes the food chain of the water and is used an indicator of the water pollution. This article presents the results of biochemical, microbiological and parasitological studies of fish caught in the Shagalaly River. A total of 106 specimens of fish belonging to the Cyprinidae family were examined. As a result, it was established that there was no ammonia in the muscles of fish meat, the reaction to hydrogen sulfide was negative, the concentration of hydrogen ions in the studied samples were in the range of 6.6 - 6.7. The number of mesophilic aerobic and facultative anaerobic microorganisms was not observed at a cultivation cell of 1 × 105, which corresponds to the norm. Coliform bacteria was not found. When determining bacterial contamination for a reductase test, the samples were discolored after more than 3 hours, which indicates the absence of reductase. Metacercariae of the Opisthorchiidae family were found by the microscopy of muscles. The infection of ide by Opisthorchis felineus was 12.1%, Metorchis bilis - 6.09%, Metorchis xanthosomus - 10.9%, Pseudamphistomum truncatum - 2.4%. Pseudamphistomum truncatum was found in the muscles of the crucian carp, the infection rate was 29.1%. Molecular genetic analysis was carried out for the species differentiation of Opisthorchis felineus and Metorchis bilis metacercariae.